2020
DOI: 10.3389/fonc.2020.556718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rehabilitation on Breast Cancer Related Fatigue: A Pilot Study

Abstract: Breast cancer fatigue (BCF) is a complex and multidimensional condition characterized by a persistent sense of physical and/or mental stiffness, resulting in a substantial impairment of health-related quality of life in breast cancer survivors. Aim of this prospective cohort study was to evaluate the feasibility and the effectiveness of a 4-week rehabilitation protocol on BCF, muscle mass, strength, physical performance, and quality of life in breast cancer (BC) survivors. We recruited adult BC women with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 51 publications
(60 reference statements)
1
56
0
1
Order By: Relevance
“…Lymphoedema, for example, is known to compound RTW challenges where there may be restrictions in mobility or heavy lifting, for example [39]. A multicomponent approach in rehabilitation may help to address wide-ranging disease and treatmentrelated side-effects that impact on RTW [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoedema, for example, is known to compound RTW challenges where there may be restrictions in mobility or heavy lifting, for example [39]. A multicomponent approach in rehabilitation may help to address wide-ranging disease and treatmentrelated side-effects that impact on RTW [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…distress could be alleviated via psychological intervention (7,8). Breast cancerrelated fatigue is also a major issue influencing quality of life, and some rehabilitation protocols like aerobic exercise could help (9). Several studies were focused on prevalence of mental illness during surgical intervention or medical treatment after diagnosing breast cancer since many cases of breast cancer are associated with physical disability and a poor quality of life after their breast cancer diagnosis with symptoms of fatigue, depression, and anxiety (10).…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that rehabilitation exercise is effective in improving the QoL in patients who have survived cancer [35,36]; in addition, referring to a supervised rehabilitation program for the fatigue reduction [37], there are no studies that have specifically addressed the rehabilitation setting impact and the psycho-emotional implications linked to the patient's personality. Kirkham et al reported how adherence to supervised exercise, delivered in a clinical setting, varies between BC patients and treatments.…”
Section: Discussionmentioning
confidence: 99%